2009
DOI: 10.2298/abs0902213k
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related health-relevant changes in natural populations of Norway rat (Rattus norvegicus Berkenhout, 1769): White blood cell counts, leukocyte activity, and peripheral organ infiltration

Abstract: Basic immune-related health-relevant changes (total and differential white blood cell counts and activity, leukocyte tissue infiltration, and related pathohistology) were assessed in wild Norway rats from urban habitats. Comparative measurements were conducted in individuals of several laboratory strains of Norway rat in order to gain insight into environmental effects on the health of wild rats. Changes in leukocyte counts and activity along with tissue infiltration were noted only in wild rats, indicating sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…No difference was observed in absolute internal organ (lung, liver and kidney) mass between wild-caught and laboratory rats. In line with our previous small-scale study (Kataranovski et al 2009b), histological analysis of organs of 89 randomly selected wild-caught rats (47 females and 42 males) demonstrated that all but 1 individual (98.9%) had evidence of tissue changes and/or signs of immune/inflammatory activity in tissue. Changes in liver were detected in 57.3% of wild rats and included acidophilic or vacuolar degeneration of hepatocytes, mixed inflammatory cell infiltrates (either in focuses or in diffuse pattern of infiltration), microapscesses as well as prominent Kupffer cells.…”
Section: General Morphometric Histoanatomical and Physiological Datasupporting
confidence: 89%
See 3 more Smart Citations
“…No difference was observed in absolute internal organ (lung, liver and kidney) mass between wild-caught and laboratory rats. In line with our previous small-scale study (Kataranovski et al 2009b), histological analysis of organs of 89 randomly selected wild-caught rats (47 females and 42 males) demonstrated that all but 1 individual (98.9%) had evidence of tissue changes and/or signs of immune/inflammatory activity in tissue. Changes in liver were detected in 57.3% of wild rats and included acidophilic or vacuolar degeneration of hepatocytes, mixed inflammatory cell infiltrates (either in focuses or in diffuse pattern of infiltration), microapscesses as well as prominent Kupffer cells.…”
Section: General Morphometric Histoanatomical and Physiological Datasupporting
confidence: 89%
“…Automated analysis of hematological parameters similar to our previous data obtained by blood smears analysis of small numbers of wild rats (Kataranovski et al 2009b) showed no differences in total peripheral blood leukocyte numbers (Table 1). Great variation in differential leukocyte numbers was evident, which resulted in lack of statistical significance between wild and laboratory individuals.…”
Section: General Morphometric Histoanatomical and Physiological Datasupporting
confidence: 83%
See 2 more Smart Citations
“…However, the picture of T cell maturation was complicated, with wild rats having higher proportions of immature CD4 + CD8 + double-positive peripheral T cells, but lower proportions of immature CD90 + CD4 + T cells, and higher proportions of CD59 + CD8 + cells (a marker involved in complement regulation) ( 22 ). Two other studies showed relatively small differences in the composition of peripheral ( 21 ) and splenic ( 19 ) mononuclear cells among wild and laboratory rats. Similarly, concentrations of circulating cytokines and chemokines were, overall, not different between wild and laboratory rats and for those that did differ (5 of 23 measured), the laboratory rats had higher cytokine concentrations than the wild rats ( 22 ).…”
Section: Immune Function In Wild Rodentsmentioning
confidence: 89%